2020
DOI: 10.3390/ani10010146
|View full text |Cite
|
Sign up to set email alerts
|

Gas Production, Digestibility and Efficacy of Stored or Fresh Plant Extracts to Reduce Methane Production on Different Substrates

Abstract: Natural compounds such as plant secondary metabolites (PSM) can be used to replace antibiotic growth promoters as rumen modifiers. In this study, the effectiveness of stored and freshly extracted Aloe vera (AV), Azadirachta indica (AZ), Moringa oleifera (MO), Jatropha curcas (JA), Tithonia diversifolia (TD) and Carica papaya (CP) crude extract and monensin on in vitro gas and methane production, organic matter digestibility (IVOMD) and volatile fatty acids (VFA) were evaluated using a total mixed ration (TMR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
(56 reference statements)
5
17
0
1
Order By: Relevance
“…Extracts solutions were administered at a dosage of 50 mg/kg of feed DM consumed while the actual dosage drenched to each animal was adjusted weekly using the previous week's feed intake. The 50 mg/kg dry matter intake (DMI) dose of extract was based on previous in vitro trials which established the effective dose at which the extracts reduced enteric methane [2,9,14]. Forty 4-month-old SAMM ram lambs with an average live weight of 28.8 ± 0.40 kg were blocked according to their body weight, and from each block randomly allocated into four dietary treatments which include (i) total mixed ration diet (TMR) + distilled water as a control, (ii) TMR + MO extract (50 mg/kg DMI), (iii) TMR + JC extract (50 mg/kg DMI) and, (iv) TMR + AV extract (50 mg/kg DMI).…”
Section: Study Area Experimental Design and Preparation Of Plant Extmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracts solutions were administered at a dosage of 50 mg/kg of feed DM consumed while the actual dosage drenched to each animal was adjusted weekly using the previous week's feed intake. The 50 mg/kg dry matter intake (DMI) dose of extract was based on previous in vitro trials which established the effective dose at which the extracts reduced enteric methane [2,9,14]. Forty 4-month-old SAMM ram lambs with an average live weight of 28.8 ± 0.40 kg were blocked according to their body weight, and from each block randomly allocated into four dietary treatments which include (i) total mixed ration diet (TMR) + distilled water as a control, (ii) TMR + MO extract (50 mg/kg DMI), (iii) TMR + JC extract (50 mg/kg DMI) and, (iv) TMR + AV extract (50 mg/kg DMI).…”
Section: Study Area Experimental Design and Preparation Of Plant Extmentioning
confidence: 99%
“…However, while some of these PSMs are capable of binding to specific receptors in neurons, intestines, and other cells and exhibit favourable physiological effects [7], others may be antinutritional and exert toxic effects on animals consuming them, depending on the type of plant or parts, or amount consumed [6,8]. Even though the use of methanolic extracts of Moringa, Jatropha and Aloe vera has been validated in vitro [2,9], nevertheless, a great deal of consideration should be given to the impact of these 'natural alternatives' on the health of animals before being recommended for wider application. For example, the phorbol esters in Jatropha curcas at a concentration above 1.45 mg/kg body weight (BW) in ruminants were found to exert reduced performance, physiological toxic effects and cause eventual death [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, studies on tropical plants such as G. sepium and E. cyclocarpum, and Y. schidigera, concluded that saponins did not reduce CH 4 production under in vitro conditions [77], and no significant effects were reported on ruminal methane production under in vivo conditions when Pelibuey sheep were fed with P. purpureum and supplemented with increasing levels of Yucca schidigera saponins (0, 1.5, 3.0, and 4.5 g/day) [78]. Akanmu et al [79] reported under in vitro conditions that the addition of 50 mg/kg of Moringa oleifera and Tithonia diversifolia extracts to a forage-based diet reduced CH 4 production without adverse effects on feed digestibility.…”
Section: Effect Of Secondary Metabolites Of Tropical Trees On Rumen Fermentationmentioning
confidence: 99%
“…Aderao [ 43 ] recommended Acacia nilotica and Ziziphus nummularia leaves, which are rich in polyphenols, to be used as a feed as they reduce methane and improve green livestock production. Akanmu et al reported that the use of crude extract ( Azadirachta indica , Moringa oleifera , Jatropha curcas , Tithonia diversifolia and Carica papaya ) as feed decreased methane production and increased digestibility [ 44 ].…”
Section: Discussionmentioning
confidence: 99%